Fabrication and characterization of a bulk micromachined polysilicon piezoresistive accelerometer. (2022) - Mukhiya, R.; Santosh, M.; Sharma, A.; Santosh Kumar, S.; Bose, S.C.; Gopal, R.; Pant, B.D.
Abstract: This paper presents the fabrication and characterization of a MEMS bulk micromachined piezoresistive accelerometer. For transduction of acceleration into output voltage, polysilicon piezoresistors are used. Due to cost effectiveness, polysilicon piezoresistors are preferred over SOI-based silicon piezoresistors. The accelerometer is designed using FEM-based MEMSCAD tool CoventorWare®. The accelerometer sensor is realized using a hybrid approach, consisting of wet and dry bulk micromachining techniques. The developed sensor is characterized for static and dynamic performance using nano-indenter and electrodynamic shaker, respectively. From static characterization, stiffness and natural frequency are found to be 7.25 kN/m and 6.78 kHz, respectively. From dynamic characterization, bandwidth and sensitivity are found to be 475 Hz and 10 mV/V/g, respectively.